2021
DOI: 10.1016/j.ekir.2021.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Information Needs of Patients With IgA Nephropathy Using an Innovative Social Media–stepped Analytical Approach

Abstract: Introduction: The number of people with kidney disease using social media to search for medical information and peer support is increasing. IgA nephropathy (IgAN) predominantly affects young adults, demographically the biggest users of social media. This article presents an innovative analysis of social media interactions to identify unmet education and information needs of patients with IgAN.Methods: Following ethical approval for the study, the IgAN Support UK Facebook group (https://www. facebook.com/groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…Although the internet was not perceived as a valuable resource regarding the science and implications of the translocation, online support groups had an important role in adaptative coping. The role of online support groups in meeting the informational and emotional needs of patients has been previously well described (Bender et al, 2011; Malik & Coulson, 2010; Vasilica et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the internet was not perceived as a valuable resource regarding the science and implications of the translocation, online support groups had an important role in adaptative coping. The role of online support groups in meeting the informational and emotional needs of patients has been previously well described (Bender et al, 2011; Malik & Coulson, 2010; Vasilica et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The role of online support groups in meeting the informational and emotional needs of patients has been previously well described (Bender et al, 2011;Malik & Coulson, 2010;Vasilica et al, 2021).…”
Section: Coping Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Healthcare professionals must be able to recognize the potential value of technology and data and ideally be involved in the development of new digital infrastructure to ensure that digital technologies work for our healthcare systems, our patients and answer the questions which traditional research methods are unable to answer. Existing research on the utilization of such technologies has found improved health behaviour and treatment compliance (Ibrahim et al, 2022), the satisfaction of patient information needs (Allen et al, 2016; Garwood‐Cross et al, 2021; Vasilica, Garwood‐Cross, et al, 2021; Vasilica, Oates, et al, 2021) and improved service metrics (Wynn & Scholes, 2022). Digital technologies can be utilized in a number of ways such as utilizing digital data to improve health research, joining up provision between services and improving patients' self‐management of conditions to influence health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Ma and colleagues collected survey data via polycystic kidney disease related Facebook groups to explore the information needs of individuals with polycystic kidney disease and their caregivers [14]. Another study also assessed the information needs of individuals with CKD, but focused on IgA nephropathy by analyzing the posts and comments of groups users of the UK IgA nephropathy Facebook group [15]. In addition, a study in UK assessed the importance of a localized online network in supporting its members dealing with kidney disease, including patients, families and caregivers [16].…”
Section: Introductionmentioning
confidence: 99%